Structural characterization and hypolipidemic activities of purified stigma maydis polysaccharides - Deng, Wenwen (Food Sci Nutr, 2019)
This study aimed to investigate structural features and antihyperlipidemic effects of the stigma maydis polysaccharide, termed SMP‐1. This polysaccharide was composed of D‐mannose, L‐rhamnose, D‐glucose, D‐galactose, L‐arabinose, D‐xylose, and D‐galacturonic acid, with a molar ratio of 1.00:0.21:1.41:1.44:0.70:0.44:0.56. The SMP‐1 was mainly bonded by (1 → 6) and (1 → 3) linkages, with various monosaccharides being evenly distributed in the main and side chains. Moreover, SMP‐1 had neither triple‐helical structure nor molecular aggregation. Importantly, the SMP‐1 could effectively bind the bile acids in vitro and significantly lower the total cholesterol, triglyceride, low‐density lipoprotein cholesterol levels, and moderately increase the high‐density lipoprotein cholesterol level in poloxamer 407‐induced hyperlipidemic mice. Moreover, pretreatment with SMP‐1 (≥300 mg/kg) could remarkably reduce fat accumulation and restore hepatocyte morphology in the liver of hyperlipidemic mice. Altogether, these findings indicated that SMP‐1 could be developed as a safe and effective food supplement for preventing and treating hyperlipidemic disorders.